Once upon a dork. 8 - Russell, Rachel Renee; Russell, Nikki; Russell, Erin; Russell, Rachel Renee (London : Simon and Schuster, 2015)
After a bump on the head, Nikki has a wild dream in which she, her BFF's Chloe and Zoey, her crush Brandon, and mean girl Mackenzie all end up playing the roles of some familiar classic fairy tale characters. Will Nikki's dream turn into a nightmare?
Originally published in the USA in 2014 as Dork Diaries 8 : Tales from a not-so-happily ever after.
b
b
Keywords: Maxwell, Nikki (Fictitious character) -- Juvenile fiction; Best friends -- Juvenile fiction; Role playing -- Juvenile fiction; Dreams -- Juvenile fiction